HUBUNGAN KADAR GULA DARAH DENGAN VISUS PADA PASIEN PASCA OPERASI KARATAK DIABETIKUM DI RSUD SAWAHLUNTO - Desy Merilla Erizon (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Diabetic cataracts are cataracts caused by diabetes mellitus. People with diabetes mellitus can show changes in the strength of refraction based on changes in sugar levels experienced. Treatment for cataracts is surgery. Cataract surgery aims to improve visual acuity and improve the quality of life of patient. The purpose of study was to determine the relationship of blood glucose levels with visual acuity on patients after cataract diabeticum surgery in Sawahlunto hospital. Data collection was taken from the patient’s medical record of 47 respondents. Sampling by accidental sampling technique. The data is finalized univariate in the form of frequency distribution and bivariate attributed to the chi squre test. The results showed mere than half (53,2%) were notnormal blood glucose after cataract diabetikum surgery, more than half (53,2%) of the visual acuity is poor after diabetic cataract surgery. From the results of the study showed a significant relationship between blood glucose with visual acuity on patients after cataract diabeticum surgery in Sawahlunto hospital with p value 0,000. The conclution of this study there is a relationship between blood glucose with visual acuity on patients after cataract diabeticum surgery in Sawahlunto hospital. Expected to health workers in providing a more comprehensive service and also a reference for health workers reviewing the results of examination of blood glucose with visual acuity.